2003
DOI: 10.1002/ajmg.b.20053
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of psychopathological symptoms: Insomnia in mood disorders and CLOCK gene polymorphism

Abstract: We investigated the possible effect of the 3111T/C CLOCK gene polymorphism on sleep disorders in a sample of 620 patients affected by major depressive disorder (MDD) and bipolar disorder (BP). We detected a significantly higher recurrence of initial (P = 0.0001), middle (P = 0.0009), and early (P = 0.0008) insomnia in homozygotes for the C variant and a similar trend concerning decreased need of sleep in BP (P = 0.0074). Other demographic and clinical features were found not related with CLOCK polymorphisms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 231 publications
(145 citation statements)
references
References 26 publications
4
134
3
4
Order By: Relevance
“…Sleep variables derived from nocturnal polysomnography did not differ between the genotypes [99]. Interestingly, clinical and restactivity data in patients with mood disorders indicate that individuals with the 3111C allele have increased occurrence of disturbed sleep both during mood episodes as well as in remission, higher motor activity levels in the evening, and a different response to lithium than patients homozygous for the T allele [102][103][104].…”
Section: Candidate Gene Approach Circadian Locomotor Output Cycles Kamentioning
confidence: 86%
“…Sleep variables derived from nocturnal polysomnography did not differ between the genotypes [99]. Interestingly, clinical and restactivity data in patients with mood disorders indicate that individuals with the 3111C allele have increased occurrence of disturbed sleep both during mood episodes as well as in remission, higher motor activity levels in the evening, and a different response to lithium than patients homozygous for the T allele [102][103][104].…”
Section: Candidate Gene Approach Circadian Locomotor Output Cycles Kamentioning
confidence: 86%
“…17 Although we did not perform any assessment of sleep patterns in our subjects, it is of interest that the rs1801260 polymorphism has previously been associated with sleep dysregulation in humans in many [31][32][33][34][35][36][37][38] but not all studies. 39 These findings, together with the present results may provide genetic evidence to support epidemiological studies associating sleep disturbance with the development of diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…31 -33 Studies using more stringent criteria to defi ne insomnia have produced more realistic and reliably modest h 2 estimates ranging from 31% to 58%. 32 , 34 , 35 Candidate gene studies have identifi ed gene variants that may be involved in the pathophysiology of insomnia, including Apo ε 4, 36 PER3 4/4 , 37 HLA DQB1 * 0602, 38 homozygous Clock gene 3111C/C Clock, 39 and short (s-) allele of the 5-HTTLPR. 40 A genomewide association study found numerous single-nucleotide polymorphisms (SNPs) signifi cantly associated with insomnia symptoms.…”
Section: Genetics Of Sleep and Insomniamentioning
confidence: 99%